The Effect of Principal Leadership, Work Climate, and Work Motivation Through Job Satisfaction Toward Teacher Performance (Educational Management, 2022)
This study aims to analyze the influence of the principal's leadership, work climate and work motivation on teacher performance with job satisfaction as an intervening variable. There are several factors that affect teacher performance including the leadership of the principal, work climate, work motivation and job satisfaction of teachers. This research was conducted at MAN 1 Semarang Regency, MAN 2 Semarang Regency and MAN Salatiga City. This research uses quantitative research methods. The population of this study were teachers at MAN 1 Semarang Regency, MAN 2 Semarang Regency and MAN Salatiga. Sampling using non-probability sampling with the selected sampling technique is purposive sampling. The sample in this study amounted to 128 respondents. The data collection technique in this study used a questionnaire. Data analysis techniques used three analytical techniques, namely descriptive statistical analysis, multiple regression analysis, and path analysis. The findings in this study indicate that the principal's leadership, work climate, work motivation and job satisfaction have a direct effect on teacher performance. And the principal's leadership, work climate, and work motivation have an indirect effect on teacher performance mediated by job satisfaction.